Information needs of internal and external stakeholders and how to respond: reporting on operations and intellectual capital. (12th February 2008) - Burgman, Roland; Roos, Goran; Boldt-Christmas, Lisa; Pike, Stephen
Numerous articles, papers and books have come to the conclusion that our traditional accounting systems do not suffice for today's companies, whose value creation often depends more on intellectual capital type resources rather than monetary or physical resources. This article focuses on the importance of measuring and reporting on intellectual capital for listed companies and the information needs of external stakeholders (the investor community) as well internal (management). It discusses the difficulties associated with disclosure of non-financial information. To conclude, it suggests guidelines for disclosure of intellectual capital from the perspective of listed companies.